2014
DOI: 10.2134/agronj2013.0467
|View full text |Cite
|
Sign up to set email alerts
|

Rye–Vetch Mixture Proportion Tradeoffs: Cover Crop Productivity, Nitrogen Accumulation, and Weed Suppression

Abstract: Cereal-legume cover crop mixtures have the potential to combine the unique strengths of the component species while taking advantage of interspeci c synergies. However, the relative proportion of each species in the mixture is likely to in uence species interactions and entail important tradeo s in cover crop performance. e objective of this study was to evaluate how the relative proportions of cereal rye (Secale cereale L.) and hairy vetch (Vicia villosa Roth) sown in mixtures in uenced cover crop biomass pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 63 publications
(92 reference statements)
8
67
1
Order By: Relevance
“…The use of a grass in combination with a legume cover crop can improve N-release synchrony. Prior to termination, grass cover crops may take up N produced by legumes, while after termination, the higher C:N ratio of grasses moderates the leaching potential of the low C:N-ratio legumes [64,65]. Recent research in Maryland demonstrated that mixtures of hairy vetch and cereal rye, residues of which have a substantively higher C:N ratio than hairy vetch alone, can slow the decay rate of cover crop residues and reduce the quantity of early season plant-available N in the soil while still providing an important source of N for corn later in the season [52,58].…”
Section: Corn Fertility Managementmentioning
confidence: 99%
“…The use of a grass in combination with a legume cover crop can improve N-release synchrony. Prior to termination, grass cover crops may take up N produced by legumes, while after termination, the higher C:N ratio of grasses moderates the leaching potential of the low C:N-ratio legumes [64,65]. Recent research in Maryland demonstrated that mixtures of hairy vetch and cereal rye, residues of which have a substantively higher C:N ratio than hairy vetch alone, can slow the decay rate of cover crop residues and reduce the quantity of early season plant-available N in the soil while still providing an important source of N for corn later in the season [52,58].…”
Section: Corn Fertility Managementmentioning
confidence: 99%
“…In many instances, these trade-offs can be predicted from the characteristics and proportions of individual component species. For example, total N accumulation of biculture residues and winter rye tissue N concentration have been positively correlated with legume proportions in rye/hairy vetch (Vicia villosa Roth) bicultures (Hayden et al, 2014). Recovery of residual soil NO 3 --N by bicultures has been shown to be intermediary between rye and legume monoculture CC (Ranells and Wagger, 1997).…”
Section: Nitrogen Benefi Ts Of Winter Cover Crop and Fall-applied Poumentioning
confidence: 99%
“…However, the biculture residue N content, grain yield, stover N, and grain N tended to fall between those values for Legume and Rye and ultimately resulted in an FNEQ similar with that of LegumePL by Year 3. While grass-legume biculture with PL may not consistently have as high FNEQ as LegumePL, there are benefits and tradeoffs when managing bicultures including N retention, weed suppression, and management costs (Brainard et al, 2011;Hayden et al, 2014).…”
Section: Fertilizer Nitrogen Equivalencementioning
confidence: 99%
“…Due to their unique ability to fix atmospheric N 2 via root nodules and produce substantial biomass and nutrient accumulations, the legume green manure (LGM) has become one of the most common and widely studied crop in the worldwide various agro-ecosystems. It has been demonstrated in different regions of the world that LGMs within a cropping system can (i) improve the grain yield of the subsequent cereal crops141516, (ii) provide net additions of N1718, maintain soil fertility and biological activity19, and (iii) reduce N fertilizer application needs2021. Consequently, growing the LGMs during the summer fallow period and incorporating them into the soil at a suitable stage is a viable method to maintain the nutrients, soil structure, and subsequent crop growth and yield.…”
mentioning
confidence: 99%